2017
DOI: 10.1049/iet-rpg.2016.0501
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of frequency reserves for high wind power generation

Abstract: Comments to Author : (1)This paper illustrates that power forecasts for different time scales as well as available wind power in real-time are modeled for future European wind power scenarios of 2020 and 2030. The reviewer suggests that the authors provide more details on the theoretical derivation. For example, the explanation of Figs. 5 and 7 need to be improved. The reviewer also suggests the authors include more simulation results in the Section of System Studies. For example, compare the performance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…From these results, it can be observed that although imbalance due to wind power forecast error is foreseen to be low in 2020, it can be expected to be quite high in the 2030 scenario. However, these imbalances can be substantially reduced by increasing the volume of secondary reserves or FRR (Das, Litong‐Palima, et al, ). Volume of secondary reserves is represented as percentage of recommended secondary reserves.…”
Section: Application Of Simulated Large‐scale Wind and Solar Pv Genermentioning
confidence: 99%
See 1 more Smart Citation
“…From these results, it can be observed that although imbalance due to wind power forecast error is foreseen to be low in 2020, it can be expected to be quite high in the 2030 scenario. However, these imbalances can be substantially reduced by increasing the volume of secondary reserves or FRR (Das, Litong‐Palima, et al, ). Volume of secondary reserves is represented as percentage of recommended secondary reserves.…”
Section: Application Of Simulated Large‐scale Wind and Solar Pv Genermentioning
confidence: 99%
“…VRE generation time series for future scenarios can be generated using stochastic time series simulation (Ekström, Koivisto, Mellin, Millar, & Lehtonen, ; Klöckl & Papaefthymiou, ; Koivisto et al, ), or meteorological reanalysis techniques (i.e., using historical weather data) (González‐Aparicio et al, ; Marinelli et al, ; Nuño et al, ; Staffell & Pfenninger, ). Such VRE generation simulation tools can be used, for example, in the estimation of adequacy of reserves in power systems (Das et al, ), in stability analyses (Flynn et al, ), in long‐term transmission system planning (Marinelli et al, ), and in electricity market studies (Traber, Koduvere, & Koivisto, ). These modeling approaches will be presented in Section 2.…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining a stable and secure operation in the electricity system with large share of VRE can be very challenging for the power system operators. Major challenges involved in operational planning are estimation of operational reserves [3], or determining the ramp requirements and flexibility for the generators. This information is then used to mitigate the impact of variability in the electric power systems.…”
Section: Introductionmentioning
confidence: 99%
“…FCR are automatic and expensive reserves activated within seconds following a power imbalance, while FRR and RR are activated within longer time frame from minutes to an hour. The responsibility of FCR is to restrict the sudden rise/decline of frequency, while FRR and RR are activated to release FCR as well as to bring the frequency back to its nominal value [4,5]. A fast release of FCR gives to the power system the ability to handle new possible consecutive power imbalances.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally volume of FCR is quantified based on n-1 security criterion [9]. A methodology is proposed in [5] to quantify volume of FCR and FRR for future power systems with high penetration of wind power to handle wind power forecast error. Availability of FCR volume is a necessary but not sufficient condition to prevent frequency instability.…”
Section: Introductionmentioning
confidence: 99%